Islamic Values and Emotional Intelligence: Implications for Character Education in the Digital Age - Huda, Taufik; Al-Rashid, Fatimah; Idris, Adam (Darussalam: Journal of Psychology and Educational, 2025)
The rapid advancement of technology presents both opportunities and challenges for character education, particularly in integrating emotional intelligence (ei) with islamic values. Emotional intelligence, which involves the ability to manage one’s emotions and understand others, is essential for character development, and when coupled with islamic principles, it can provide a strong moral foundation. This study explores the implications of combining islamic values, such as empathy, patience, and self-regulation, with ei to enhance character education in the digital age. It examines how digital platforms can support the development of emotional skills while reinforcing ethical behavior rooted in islamic teachings. The research highlights that integrating these values in educational practices can foster emotionally intelligent, ethically grounded individuals capable of navigating the complexities of the digital world.